Information management : strategies for gaining a competitive advantage with data - McKnight, William (Consultant) (Savvy manager's guides., 2014)
This book covers the following topics: the importance of information management and analytics to business, and how data warehouses are used; the technologies and data that advance an organization, and extend data warehouses and related functionality; Big Data and NoSQL, and how technologies like Hadoop enable management of new forms of data; agile development, modern business intelligence, and organizational change management.